5(b+3)=3b+23

Simple and best practice solution for 5(b+3)=3b+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(b+3)=3b+23 equation:


Simplifying
5(b + 3) = 3b + 23

Reorder the terms:
5(3 + b) = 3b + 23
(3 * 5 + b * 5) = 3b + 23
(15 + 5b) = 3b + 23

Reorder the terms:
15 + 5b = 23 + 3b

Solving
15 + 5b = 23 + 3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-3b' to each side of the equation.
15 + 5b + -3b = 23 + 3b + -3b

Combine like terms: 5b + -3b = 2b
15 + 2b = 23 + 3b + -3b

Combine like terms: 3b + -3b = 0
15 + 2b = 23 + 0
15 + 2b = 23

Add '-15' to each side of the equation.
15 + -15 + 2b = 23 + -15

Combine like terms: 15 + -15 = 0
0 + 2b = 23 + -15
2b = 23 + -15

Combine like terms: 23 + -15 = 8
2b = 8

Divide each side by '2'.
b = 4

Simplifying
b = 4

See similar equations:

| 3x-8=56 | | 4x+9-2x+2=3x-5-x | | 12-6x=2x+10 | | 11x+32=56 | | 3x-4=-x+6 | | U=5(6n+31)+9(n+1) | | 7x-2=3x-22 | | 40x+70y=6000 | | 3w+4=5m+7-m | | X+3x+2y= | | 2(3-x)+7=2x-(x-4) | | 6x+12=12x+6 | | 0.5x+1=2.5x | | 4y-5x=60 | | 8z=2xb | | 12=2(x-4)-6 | | 2(3-x)+7=2x-4(x-4) | | 3(h+4)+5=35 | | (1+x)(1+z)= | | 10x^2+1210=0 | | 2ydx-2xdy=0 | | 18i-14i= | | 5x+-6+2=7x+-6 | | .6k-(k+.25)=.05(k+1) | | Z-4z=9z-9-z | | 2(5-2v)=5(v-5) | | 87-n=13 | | 24n^3+30n^2=0 | | -21a+28a-6=10 | | 4[(12+5)-1024]= | | 5y-15+6=5y+8-1x+17 | | 4x^2+6x+1=2x^2+6x-6+1 |

Equations solver categories